Knowledge of sexually transmitted diseases and condom use among female street sex workers in Padua - Veller-Fornasa, Cleto (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Objectives: The aim of the present study was to investigate knowledge of sexually transmitted diseases (STDs) and condom use in a population of young female street sex workers from eastern Europe and other non-EU countries basedin the Padua area (north-eastern Italy). To assess whether any aspects oftheir behavior might foster the spread of STDs. Study design: Street sex workers (prostitutes) were approached on the streets or during non-STD medicalappointments, their knowledge of STDs and condom use were evaluated. They were asked to answer an anonymous questionnaire comprising 16 questions. Results: 98 of them cooperated. Over one third of the sample frequently did not use a condom. This finding was inversely correlated with their age and educational level. Almost all the street sex workers were aware of AIDS but far less of other STDs. Most were almost totally unacquainted with some of them. We found a statistically significant correlation between condom use and their age, and between condom use and educational level. Conclusions: Sex workers often engaged in unprotected intercourse with clients, they practiced their profession even in the presence of STD-related symptoms and did not use a condom during intercourse with non-paying partners or pimps. The irresponsible behavior of some Italian paying partners prepared to pay extra for unprotected sex, increases the risk of acquiring STDs. The intercourse with female street sex workers can be considered a risk behavior for contracting STDs.
Keywords: Condoms; Kondomi; prostitucija; prostitutke; Sexually Transmitted Diseases; spolne bolezni; Spolno prenosljive bolezni